EQUIPMENT DESIGN AND TESTING TRANSFER VOLTAGE REFERRING TO IEC 156 STANDARD USING VIRGIN COCONUT OIL (VCO) WITH OIL TEMPERATURE CONDITIONING - Ansyori Ansyori; Irsyadi Yani; Eric Rahman (Indonesian Journal of Engineering and Science (IJES), 2021)
Isolation is a separator between conductors in electrical equipment that prevents flashover, resulting in a short circuit or electrical failure. Isolation is critical in electrical appliances, exceptionally High Voltage Power Equipment (HVPE), to ensure the safety of circuit breakers, capacitors, and transformers. In addition to being an isolator, the insulating liquid material also serves to cool the heat generated by electrical appliances. Isolator with mineral oil-based transformer has various environmental issues, including non-biodegradability, non-renewability, and rarity. Because it is environmentally safe and extensively used, virgin coconut oil (VCO) is an alternative transformer oil insulation. This study aims to determine the properties of Virgin Coconut Oil (VCO) breakdown voltage using the IEC 156 standard and oil temperature conditioning. According to the test results, the oil breakdown voltage before heating (at room temperature) is 14 kV, which is much below the IEC 156 standard, and the breakdown voltage after heating at 90 ° is 35 kV, and 110 ° is 40 kV, which is even higher than the IEC 156 requirement